The relationship between fragmented QRS and functional significance of coronary lesions - Korkmaz, Ahmet; Yildiz, Abdulkadir; Demir, Mevlut; Ozyazgan, Burcu; Sahan, Ekrem; Acar, Burak; Guray, Umit; Ileri, Mehmet; Elalmis, Ozgul Ucar (My University, 2017)
Background: Recently fragmented QRS (fQRS) on electrocardiography (ECG) has been introduced as a predictor of myocardial scarring and myocardial ischemia in coronary artery disease (CAD).